Characteristics of BRAFV600E Mutant, Deficient Mismatch Repair/Proficient Mismatch Repair, Metastatic Colorectal Cancer: A Multicenter Series of 287 Patients. (31st May 2019) - Fouchardière, Christelle; Cohen, Romain; Malka, David; Guimbaud, Rosine; Bourien, Héloïse; Lièvre, Astrid; Cacheux, Wulfran; Artru, Pascal; François, Eric; Gilabert, Marine; Samalin‐Scalzi, Emmanuelle; Zaanan, Aziz; et al.
Abstract: Background: BRAF V600E mutations occurring in about 10% of metastatic colorectal cancers (mCRCs) are usually associated with a poor outcome. However, their prognostic factors are unknown. Materials and Methods: We built a multicenter clinico‐biological database gathering data from patients with BRAF V600E ‐mutant mCRC treated in one of the 16 French centers from 2006 to 2017. The primary endpoint was to identify prognostic factors using a Cox model. Results: We included 287 patients (median age, 67 years [28 –95]; female, 57%). Their median overall survival was 20.8 months (95% confidence interval [CI], 17.97–27.04), and median progression‐free survival in the first‐line setting was 4.34 months (95% CI, 3.81–5.03). Chemotherapy regimen and biological agents (antiangiogenic or anti‐epidermal growth factor receptor) were not associated with overall and progression‐free survival. Stage IV disease (synchronous metastases) and absence of curative‐intent surgery were statistically associated with poor overall survival. Among the 194 patients with mismatch repair (MMR) status available, overall survival was significantly longer in patients with deficient MMR tumors compared with those with proficient MMR tumors (adjusted hazard ratio = 0.56; p = .009). Conclusion: Despite that BRAF V600E ‐mutant mCRCs are associated with poor overall and progression‐free‐survival, patients with deficient MMR tumors and/or resectable disease experienced a longer survival. These results highlight the importance of MMR testing and resectability discussion in patients with BRAF V600E mCRC in day‐to‐day practice. Implications for Practice: Mismatch repair (MMR) testing and resectability discussion in patients with BRAF V600E metastatic colorectal cancer (mCRC) should be performed in day‐to‐day practice to steer treatment decision making in patients with BRAF V600E ‐mutant mCRC. Abstract : This article describes the real‐life management of BRAF V600E ‐mutant metastatic colorectal cancer in a large cohort of patients treated in 16 French centers from 2006 to 2017. Potential prognostic factors to steer treatment decisions are identified.